2020
DOI: 10.1155/2020/9638548
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Antibacterial Activities of the Essential Oil of Moroccan Tetraclinis articulata (Vahl) Masters

Abstract: The purpose of this study is to evaluate and compare the antioxidant and antibacterial activities of essential oil isolated from Tetraclinis articulata (Vahl) leaves, Masters originating in Morocco (Benslimane Region, Atlantic-influenced plain). The analysis of the major compounds of essential oil was performed by gas chromatography and mass spectrometry, and this oil is dominated by bornyl acetate (35.05%), camphor (11.17%), and α-pinene (10.84%). The antioxidant properties were evaluated by the test of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…The results of the present investigation revealed that (AJ) EO has potent antibacterial and antifungal potentials against certain strains of microbial species. Actually, bornyl acetate, the study’s main molecule, has long been recognized as a potent antimicrobial agent, according to numerous published studies [ 36 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present investigation revealed that (AJ) EO has potent antibacterial and antifungal potentials against certain strains of microbial species. Actually, bornyl acetate, the study’s main molecule, has long been recognized as a potent antimicrobial agent, according to numerous published studies [ 36 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been used as a diuretic, antipyretic, anti-rheumatic and oral hypoglycemic (Bellakhdar et al, 1982;Ziyyat et al, 1997). In parallel, various biological activities have been reported for extracts and essential oils (seeds, leaves, aerial parts) such as cytotoxic (Buhagiar et al, 1999;Aouinty et al, 2006), vasorelaxant (Zidane et al, 2014), antimicrobial (Bourkhiss et al, 2007a;Abi-Ayad et al, 2011;Chikhoune et al, 2013;Djouahri et al, 2016;Ben Ghnaya et al, 2016;Ibrahim et al, 2017;Rabib et al, 2019;2020), antioxidant and anti-inflammatory activities (Bourkhiss et al, 2010;Djouahri et al, 2013). The antimicrobial activity of T. articulata essential oil has been the subject of a many studies.…”
Section: Introductionmentioning
confidence: 99%
“…Another oil sample isolated from the leaves of T. articulata exhibited very good sensitivity against six bacteria: Salmonella enterica, Klebsiella pneumoniae, Listeria monocytogenes, Pseudomonas aeruginosa, S. aureus, E. coli, Fusarium culmorum, Aspergillus flavus and Candida albicans, with inhibition zones diameters in the range of 11.5 -25.3 mm and MIC values ranging between 0.25 and 50 µg/mL (Djouahri et al, 2016). Rabib et al (2019;2020) also reported very low MICs values (1.56 -50 µg/ml) for leaves essential oil of T. Articulata, against Pseudomonas aeruginosa, S. aureus and E. coli. Ibrahim et al in 2017 reported on the antibacterial activity of T. articulata leaf oil.…”
Section: Introductionmentioning
confidence: 99%
“…Medicinal and aromatic plants (MAPs), in their entirety or their separated parts, are used as they are or can be further processed by extraction of essential oils and are considered an important resource in various fields, such as pharmaceutical, flavor and fragrance, perfumery, and cosmetic industries [ 1 ]. Essential oils from medicinal and aromatic plants are a very interesting source of secondary metabolites because of their many different biological properties, such as cytotoxic [ 2 ], anti-inflammatory [ 3 ], antioxidant [ 4 ], insecticidal [ 5 ], antifungal [ 6 ] and antimicrobial [ 7 , 8 , 9 ], many of which are of increasing interest in the field of human and animal health. In recent years, the development of antibiotic resistance represents the major issue in medical microbiology and the search for new weapons against antibiotic resistances has led to the search of new sources of potential antimicrobials.…”
Section: Introductionmentioning
confidence: 99%